Between 1992-2005 there were 8 tsunamis occurred in Indonesia. At 17 July 2006 tsunami reached the southern coast of West Java, Cilacap and Yogyakarta. Tsunamis had caused heavy destruction and death. The aim of the study is to find out spatially the potential of inundation area by tsunami wave based on the distribution of inundation extent of different run up. The run up of 7.5 m flooded 4% from whole study area. 36% of the area was flooded by 15 m run up. When the run up was 7,5 m, some area - Anita Zaitunah; Cecep Kusmana; I Nengah Surati Jaya; Oteng Haridjaja (Forum Pasca Sarjana, 2011)
Between 1992-2005 there were 8 tsunamis occurred in Indonesia. At 17 July 2006 tsunami reached the southern coast of West Java, Cilacap and Yogyakarta. Tsunamis had caused heavy destruction and death. The aim of the study is to find out spatially the potential of inundation area by tsunami wave based on the distribution of inundation extent of different run up. The run up of 7.5 m flooded 4% from whole study area. 36% of the area was flooded by 15 m run up. When the run up was 7,5 m, some areas were flooded reaching 200 m from the coast and there were also some points going further to 1 km. The run up of 15 m moved further to 4,5 km. The information on the distance and extent of inundation from some possible run up of tsunami become an input on potential areas flooded by water and having destruction. Key words: tsunami, inundation, coastal area, West Java